Young bisexual women's sexual health care experiences in Australian rural general practice. (3rd April 2019) - Grant, Ruby; Nash, Meredith
Abstract: Objective: To examine how young bisexual women in rural Tasmania experience routine sexual health care in general practice settings. Design: Semi‐structured interviews with bisexual women were used for this study. Self‐selected and purposive sampling were used to recruit women in 2015. Participants were recruited via community social media pages and a not‐for‐profit organisation supporting same‐sex attracted rural youth. Data were analysed thematically. Setting: Regional and rural areas in the north and south of Tasmania, Australia. Participants: Fifteen bisexual women, 18‐26 years of age, with experience seeking sexual health care in Tasmania. Main outcome measure(s): Semi‐structured interviews explored women's experiences of inclusive sexual health care. Results: Four key themes emerged from the thematic analysis: (a) issues of health care accessibility in rural Tasmania; (b) the importance of visual signs of inclusivity in rural clinics; (c) practitioner attitudes; and (d) use of inclusive, gender‐neutral language. Conclusions: Rural bisexual women prefer practitioners who make meaningful efforts to be inclusive and take a non‐judgmental approach to sexual health care. Additional resources are needed to support rural communities and their health care providers to prioritise inclusive health practices.